Do sensorimotor insoles improve gait safety in patients with Parkinson’s disease on a short scale? - Maurer, Lisa K.; Maurer, Heiko; König, Manuel; van Munster, Marlena; Haen, Saskia; Pedrosa, David J.; Justus Liebig University Giessen (My University, 2024)
Introduction: Parkinson’s disease (PD) often leads to gait abnormalities, increasing the risk of falls and affecting daily life. Sensorimotor insoles aim to enhance foot sensitivity, potentially improving gait stability. Methods: This study examined whether there are short-term effects of sensorimotor insoles on neural activation (measured by EEG), kinematic gait parameters (speed, cadence, step length, and step-length variability), and subjective gait stability in PD patients. Sixteen individuals suffering from PD completed a gait task while wearing sensorimotor and placebo insoles, respectively. Results: The results showed no significant changes in kinematic parameters with the sensorimotor insoles. Subjective ratings of gait stability and attentional control of gait improved on average with the sensorimotor insoles, but again did not reach statistical significance. There was no significant reduction in alpha-band activity, indicating no improvement in sensorimotor processing. Conclusion: The immediate impact of sensorimotor insoles on sensorimotor processing and gait characteristics in PD patients remains inconclusive. The small sample size limited the statistical power, highlighting the need for larger studies to comprehensively assess efficacy. Further research should investigate the long-term effects and potential benefits on disability measures in PD patients.
Keywords: ddc:796